Pancaragam Surabaya Tempo Dulu: Perjuangan Kelas, Simbolisme Kota, dan Fluktuasi Ekonomi - Garadian, Endi Aulia (Masyarakat Sejarawan Indonesia, 2018)
This essay reviews three books covering the history of Surabaya. The three books reviewed provide an important overview of how Surabaya became a multi-dimensional space of contestation among interests, ranging from social, political to economic. Generally speaking, this review essay is written to show important literatures that is worth to read for anyone wishing to study Surabaya. Surabaya in the past, based on the above three books, contained of economic battles and territorial seizures. It is as if the city is destined for always being a battleground of various interst of certain groups, both economically and politically.